Atherosclerotic Carotid Stenoses of Apical versus Body Lesions in High-Risk Carotid Stenting Patients - Park, S.-T.; Kim, J.K.; Yoon, K.H.; Park, S.-O.; Park, S.W.; Kim, J.S.; Kim, S.J.; Suh, D.C. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Different lesion locations in the atherosclerotic carotid bulb stenosis have not been clearly defined. We sought to evaluate 2 locations of carotid bulb stenosis in high-risk patients and to determine the relationship of each location to atherosclerotic risk factors and clinical features. MATERIALS AND METHODS: Atherosclerotic carotid plaques of apical versus body lesions, defined according to the area and extent of plaque involvement, were retrospectively analyzed in 200 consecutive high-risk patients who underwent carotid stent placement because of ≥50% symptomatic stenosis. We evaluated interobserver concordance and assessed each type of lesion relative to 13 atherosclerotic risk factors, mode of symptom presentation, infarct pattern, procedure-related factors, and clinical outcomes, by univariate and multivariable logistic regression analysis. RESULTS: Interobserver concordance showed good agreement for differentiating apical and body lesions (κ = 0.745). Univariate analysis revealed that apical lesions (n = 108, 54%) were associated with pseudo-occlusion (P = .027), older age (P = .073), and alcohol intake (P = .080), whereas body lesions (n = 92, 46%) were associated with hyperlipidemia (P = .001), a wedge-shaped cortical infarct pattern (P = .057), and hyperperfusion syndrome (P = .083). Multivariable logistic regression analysis adjusted by age revealed that hyperlipidemia (P = .002; OR, 3.462; 95% CI, 1.595–7.515) and hyperperfusion (P = .026; OR, 6.727; 95% CI, 1.261–35.894) were independent predictors of body-type lesions. CONCLUSIONS: Atherosclerotic carotid bulb stenosis was found to have 2 distinct locations, body and apical. Hyperlipidemia and cortical wedge-shaped infarcts were more frequently associated with body than with apical stenosis at the time of presentation. CCAcommon carotid arteryCIconfidence intervalECAexternal carotid arteryFEVforced expiratory volumeICAinternal carotid arterymRSmodified Rankin scaleORodds ratioNASCETNorth American Symptomatic Carotid Endarterectomy TrialNIHSSNational Institutes of Health Stroke ScaleWSSwall shear stress